Ignorance is Strength - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2021)
Colin Harrison's novel The Finder (2008) uncovers the hidden hierarchy of differential information. We live in a knowledge economy, or so they say. And in the world of finance, knowledge is power: the power to buy assets before their price appreciates. This knowledge-as-power, though, is profitable only when exclusive. Common knowledge – no matter how sophisticated and complex – is never profitable. Only differential knowledge – i.e., knowledge that is unavailable to others or superior to what they have – can yield a `return'. This differential prerequisite explains why every entity in the pyramid of financial information – whether a person or an organization – has no more than a partial vista, with the remaining view blurred by enforced opaqueness and power-backed misinformation. The different vistas are also deeply formative. Individual `actors' may feel empowered by what they know, but in practice, what they know serves to frame their thoughts and direct their actions – usually without them ever knowing it. Even those at the very top – indeed, especially those at the very top – are slaves to their knowledge, however superior.
Keywords: P16; D8; 330; finance; differential information; literature; power